Annealing induced microstructure engineering of antimony tri-selenide thin films - Haque, F.; Elumalai, Naveen Kumar; Wright, M.; Mahmud, M.; Wang, D.; Upama, M.; Xu, C.; Uddin, A. (Pergamon, 2018)
The presented work demonstrates the effect of annealing on the structural, surface morphology and optical properties of Antimony Triselenide (Sb2Se3) thin films deposited by thermal evaporation. Two sets of thin films of Sb2Se3 were grown on soda lime glass (SLG) substrates by thermal evaporation with and without substrate heating. Both sets of films were then annealed at three distinct temperatures (100 °C, 200 °C and 300 °C) to study the effects of annealing on the microstructure. Analysis using XRD (X-Ray Diffraction) characterization revealed that the as-deposited films without substrate heating exhibit an amorphous nature, whereas the films grown with concurrent substrate heating are polycrystalline with orthorhombic structure. The films annealed at high temperature with concurrent substrate heating possess smooth and continuous grain morphologies. The effect of annealing was also found to have significant impact on the band gap and optical properties of the Sb2Se3 thin films.